1996
DOI: 10.1111/j.1365-2222.1996.tb00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐associated anaphylaxis: 20 years of reporting in the Netherlands (1974–1994) and review of the literature

Abstract: Summary Background Since 1963, the Drug Safety Unit of the Dutch Inspectorate for Health Care (DSU) holds a voluntary reporting system. Objective To analyse all reports received in the years 1974 to 1994, registered as anaphylaxis or as a diagnosis that could contain cases of anaphylaxis. Methods All reports were classified as probable or possible anaphylaxis according to previously described criteria and the causal relationship between exposure and anaphylaxis was assessed. Results Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…As our meta‐analysis revealed no beneficial effect of anticoagulants on the occurrence of flap failure of the FRFF, the use in daily practice seems not justifiable. Moreover, as some anticoagulants, such as dextrans, have shown a higher risk of systemic complications, including anaphylaxis, renal failure and adult respiratory distress syndrome, the risk of harm of these anticoagulants simply outweighs the lack of benefit . In addition, because of the lack of effect, administering anticoagulants to prevent flap failure will probably not be cost‐effective.…”
Section: Discussionmentioning
confidence: 99%
“…As our meta‐analysis revealed no beneficial effect of anticoagulants on the occurrence of flap failure of the FRFF, the use in daily practice seems not justifiable. Moreover, as some anticoagulants, such as dextrans, have shown a higher risk of systemic complications, including anaphylaxis, renal failure and adult respiratory distress syndrome, the risk of harm of these anticoagulants simply outweighs the lack of benefit . In addition, because of the lack of effect, administering anticoagulants to prevent flap failure will probably not be cost‐effective.…”
Section: Discussionmentioning
confidence: 99%
“…Patients develop urticaria, angioedema or anaphylaxis within seconds to the first hour after taking one NSAID or NSAIDs from the same group, while tolerating others nonrelated . Mostly involved drugs are pyrazolones, paracetamol, diclofenac and ibuprofen . Subsequent NSAIDs intake can induce anaphylaxis .…”
Section: Phenotypes In the Eaaci Classificationmentioning
confidence: 99%
“…A recent analysis of a voluntary adverse drug reaction reporting scheme in Holland identified glafenine as a major cause of anaphylaxis in Holland (110), while a review of 266 cases in the United States showed drugs to be the cause in 20% of cases, NSAIDs accounting for half of the drug-induced cases (111). Penicillin may cause a variety of hypersensitivity reactions, including anaphylaxis and serious cutaneous reactions.…”
Section: (Table 2)mentioning
confidence: 99%